2018
DOI: 10.1111/jcmm.13542
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol protects mice against SEB‐induced acute lung injury and mortality by miR‐193a modulation that targets TGF‐β signalling

Abstract: Staphylococcal enterotoxin B (SEB) is a potent superantigen produced by Staphylococcus aureus that triggers a strong immune response, characterized by cytokine storm, multi‐organ failure, and often death. When inhaled, SEB can cause acute lung injury (ALI) and respiratory failure. In this study, we investigated the effect of resveratrol (RES), a phytoallexin, on SEB‐driven ALI and mortality in mice. We used a dual‐exposure model of SEB in C3H/HeJ mice, which caused 100% mortality within the first 5 days of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 54 publications
(125 reference statements)
3
56
0
Order By: Relevance
“…Lung tissues were also smashed using a Stomacher 80 Biomaster lab blender (Metrohm USA, Riverview, FL) in 10 ml of RPMI-1640 medium, lysed with Red Blood Lysing Buffer (Sigma-Aldrich, St. Louis, MO, USA) to remove red blood cells, washed with PBS, filtered and resuspended in PBS supplemented with 5% FCS. Then lungassociated mononuclear cells were isolated from lung cell suspensions in Ficoll-Histopaque ® -1077 (Sigma-Aldrich) at a 1:1 ratio under 350 g of centrifugation for 30 min, as described (Alghetaa et al, 2018). The lung-associated mononuclear cells were stored immediately in TRIzol reagent at −80 C freezer for RNA sequencing.…”
Section: Collection Of Lung Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung tissues were also smashed using a Stomacher 80 Biomaster lab blender (Metrohm USA, Riverview, FL) in 10 ml of RPMI-1640 medium, lysed with Red Blood Lysing Buffer (Sigma-Aldrich, St. Louis, MO, USA) to remove red blood cells, washed with PBS, filtered and resuspended in PBS supplemented with 5% FCS. Then lungassociated mononuclear cells were isolated from lung cell suspensions in Ficoll-Histopaque ® -1077 (Sigma-Aldrich) at a 1:1 ratio under 350 g of centrifugation for 30 min, as described (Alghetaa et al, 2018). The lung-associated mononuclear cells were stored immediately in TRIzol reagent at −80 C freezer for RNA sequencing.…”
Section: Collection Of Lung Tissuesmentioning
confidence: 99%
“…The portions of lung-associated mononuclear cells were used in the measurement of proton efflux rate. Also, broncho-alveolar lavage fluid (BALF) was collected from these euthanized mice according to the procedure described by Alghetaa et al (2018).…”
Section: Collection Of Lung Tissuesmentioning
confidence: 99%
“…Resveratrol (Res), a phytoalexin antioxidant from red grapes, has anti‐inflammatory properties . Studies in vivo have confirmed that Res can attenuate the severity of ALI in animal models . Res or Res‐curcumin hybrids can significantly attenuate disease severity of ALI, accompanied with lower production of pro‐inflammatory cytokines and chemokines, such as TNF‐alpha, IL‐1beta, IL‐6, IL‐12, IL‐33, MIP‐2 and IL‐18.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Studies in vivo have confirmed that Res can attenuate the severity of ALI in animal models. 9,10 Res or Res-curcumin hybrids can significantly attenuate disease severity of ALI, accompanied with lower production of pro-inflammatory cytokines and chemokines, such as TNF-alpha, IL-1beta, IL-6, IL-12, IL-33, MIP-2 and IL-18. In contrast, the anti-inflammatory cytokines and molecular mediators, such as IL-10, heme oxygenase-1 (HO-1),Nrf2…”
mentioning
confidence: 99%
“…, which is embedded in a CpG island, has been identified as a tumor suppressive miRNA in several cancers such as oral carcinoma, lung cancer and colorectal cancer [27][28][29][30][31][32][33]. Apart from cancers, it is disclosed that miR-193a is downregulated in intestinal inflammation in colitis, and upregulation of miR-193a promotes anti-inflammatory activities via targeting apoptotic pathways death receptor-6 (DR6) [34]. Hence, these previous evidences reveal that miR-193a influence cells activities in diverse diseases, thereby devoting to these disease developments and progressions, whereas few evidences of miR-193a in affecting I/R injury myocardial cells have been reported.…”
Section: Discussionmentioning
confidence: 99%